HIV-related stigma and associated factors: a systematic review and meta-analysis - Dessie, Zelalem G.; Zewotir, Temesgen (Frontiers in Public Health, 2024)
Background: It has been recognized that HIV-related stigma hinders efforts in testing, treatment, and prevention. In this systematic review, we aimed to summarize available findings on the association between risk of HIV stigma versus age, social support, educational status, depression, employment status, wealth index, gender, residence, knowledge about HIV, marital status, duration since diagnosed and disclosure status using a large dataset from a number of studies.Method: Electronic databases including Scopus, Medline/PubMed, Web of Sciences (WOS), Cochrane Library, Google Scholar, and Open Research Dataset Challenge were systematically searched till 15 April 2023. Regardless of language, publishing date, or geographic location, we included all forms of HIV-stigma studies. The inclusion criteria were met by 40 studies with a total of 171,627 patients. To pool the estimate and evaluate publication bias and sensitivity analysis, a mixed-effect model was used.Results: Significantly lowering the likelihood of HIV-related stigma included older age, social support, greater education, higher socioeconomic status, good knowledge of HIV, and longer years of living with HIV. On the other hand, depression, people living in rural, female respondents, and not disclosing their HIV status were significantly associated with a high risk of HIV-related stigma.To combat systemic HIV-associated stigma, developing wholesome and comprehensive social methods through community-level HIV awareness raising is crucial. In addition to activism, local economic development is crucial to creating thriving communities with strong social fabric.